Kontribusi Pemanfaatan Fasilitas Belajar dan Etos Kerja Guru terhadap Efektifitas Pembelajaran di Madrasah Ibtidaiyah Negeri (MIN) Neglasari Kabupaten Ciamis - Munawaroh, Munawaroh; Arifudin, Yadi Fahmi (Asosiasi Mahasiswa Program Pascasarjana | Institut Agama Islam Darussalam | IAID | Ciamis | Jawa Barat, 2017)
This study found several findings: First, the use of learning facilities contribute significantly to the effectiveness of learning at MIN Neglasari. The better the utilization of learning facilities, the learning process will be more effective. This conclusion is obtained based on correlation test results that produce correlation coefficient of 0.71 (very high correlation or very strong). Second, teacher work ethic contribute significantly to the effectiveness of learning at MIN Neglasari. The higher the work ethic of teachers, the learning process will be more effective. This conclusion is obtained based on correlation test that yields correlation coefficient of 0.688 (correlation strong or high). Third, the utilization of learning facilities and work ethic of teachers together contribute to the effectiveness of learning in MIN Neglasari. The more optimal the utilization of learning facilities and the higher the work ethic of teachers, the learning process will be more effective. This conclusion is obtained after a double correlation test resulted in a correlation coefficient of 0.714 (very high or very strong correlation). This result also shows that the utilization of learning facilities and work ethic of teachers together contributes 51% to the effectiveness of learning in MIN Neglasari Ciamis